Governing Road Freight in Eastern and Central Canada: Public Sector Perceptions of Goods Movement Decarbonization - Katsanis, Alexi; Assaf, Gabriel (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2025)
Road freight governance and decarbonization are often addressed separately in both academic research and professional practice, despite road freight being a significant source of carbon emissions in Canada. This article addresses that gap by examining how public-sector staff perceive intergovernmental relationships related to road freight decarbonization. Through semi-structured interviews with planners and engineers in Ontario, Quebec, New Brunswick, and Nova Scotia, we found that decarbonizing road freight is generally a low priority within broader transportation roles although there is strong interest in developing policies and strategies to reduce emissions from road freight.